2022
DOI: 10.3390/buildings12081258
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Modeling of a Historical Building Wall: Using Long-Term Monitoring Data to Understand the Reliability and the Robustness of Numerical Simulations

Abstract: Thermal modeling of building components plays a crucial role in designing energy efficiency measures, assessing living comfort, and preventing building damages. The accuracy of the modeling process strongly depends on the reliability of the physical models and the correct selection of input parameters, especially for historic buildings where uncertainties on wall composition and material properties are higher. This work evaluates the reliability of building thermal modeling and identifies the input parameters … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 40 publications
0
9
0
Order By: Relevance
“…Although it is more straightforward than other approaches, the calibration with the parametric method gives a result very close to the experimental data. Moreover, past analyzes [24] have also shown that this approach provides a good calibration. In fact, in [24], it was seen that calibration with more sophisticated optimization methods (e.g.…”
Section: Resultsmentioning
confidence: 88%
See 3 more Smart Citations
“…Although it is more straightforward than other approaches, the calibration with the parametric method gives a result very close to the experimental data. Moreover, past analyzes [24] have also shown that this approach provides a good calibration. In fact, in [24], it was seen that calibration with more sophisticated optimization methods (e.g.…”
Section: Resultsmentioning
confidence: 88%
“…Sensors were installed on the external and internal surfaces, as well as within the wall, during the renovation, as shown in Figure 2. Detailed information on the monitoring system can be found in [23,24]. On the outside, a pyranometer (Hukseflux SR05), a driving rain gauge (SMT -RS1119), a surface temperature sensor (thermocouples), and a temperature and humidity sensor (E + E EE060) were installed.…”
Section: Case Studymentioning
confidence: 99%
See 2 more Smart Citations
“…The monitoring system captured climatic conditions over a span of five years, providing continuous measurements both inside and outside the building, as well as within the retrofitted wall at three different depths. Further details on data collection methodologies are elucidated in references [1] , [2] , [3] , [4] , [5] . Data format Raw Analyzed Description of data collection Data were collected every five minutes from varying conditions within and around a retrofitted historic building over a span of five years.…”
mentioning
confidence: 99%